산림바이오매스 확대보급과 산업화에 관한 연구 - 석현덕 (한국농촌경제연구원, 2008)
The aim of the study is to devise industrializations of pellet which is the most economical and environmentally friendly resource among renewable resources. If 200,000㏊ of forests are managed annually and by-products are collected for biomass solid fuels from them, 273,684 tons of heating fuels from fossil fuels can be saved annually. This induces an import substitution of fossil fuels to the amount of 441.8 billion wons and the effects of 20,000 job creation annually. In addition, 990 thousand tons of carbon emission can be reduced. Financial rate of returns for pellet production can be over 10% in case of biomass collection costs are reduced to the 70% of a total cost, while economic rate of returns are over 30% on the same condition. Therefore, an economic feasibility for pellet production facilities with reduction of collecting cost of forest biomass is quite high. In order to reduce the collection cost of forest biomass, projects such as constructing intensive forest roads, mechanizing forest practices, and establishing biomass collecting system should be launched.